Sejarah dan Karakteristik Sastra Anak - Sitti Hadijah; Rahma Ashari Hamzah; Ardiana Pratiwi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This research emerged from the lack of understanding of the role of Indonesian language and literature in the context of education and cultural preservation efforts. The purpose of this study is to examine the historical development and position of Indonesian language and literature as a means of unification and media in the formation of national character. The method used is qualitative with a literature study approach. The results of the study show that Indonesian language and literature continue to develop over time, and have a significant role in shaping national identity. In conclusion, both need to be preserved and developed to remain relevant in facing global challenges.